Quantitative assessment of nocturnal neural respiratory drive in children with and without obstructive sleep apnoea using surface EMG. Issue 5 (20th March 2019) - Chuang, Sandra Y.; Teng, Arthur; Butler, Jane; Gandevia, Simon; Narang, Indra; Briggs, Nancy; Selvadurai, Hiran; Jaffe, Adam
Abstract : New Findings: What is the central question of this study? Recent studies have suggested potential utility of non‐normalized respiratory muscle EMG as an index of neural respiratory drive (NRD). Whether NRD measured using non‐normalized surface EMG of the lateral chest wall overlying the diaphragm (sEMGcw) recorded during nocturnal clinical polysomnography can differentiate children with and without obstructive sleep apnoea (OSA) is not known. What is the main finding and its importance? Non‐normalized sEMGcw was increased in children with OSA and an additional group of snoring children without OSA but subjectively increased respiratory effort compared with primary snorers. The sEMGcw has potential clinical utility in evaluation of children with sleep‐disordered breathing as an objective, non‐invasive, non‐volitional marker of NRD. Abstract: Our aim was to investigate whether neural respiratory drive measured by non‐normalized surface EMG recorded from the chest wall overlying the diaphragm (sEMGcw) differentiates children with and without obstructive sleep apnoea (OSA). Polysomnography data of children aged 0–18 years were divided into the following three groups: (i) primary snorers (PS); (ii) snoring children without OSA but with increased work of breathing (incWOB; subjective physician report of increased respiratory effort during sleep); and (iii) children with OSA [obstructive apnoea–hypopnoea index (OAHI) >1 h −1 ]. Excerpts of sEMGcw obtained during tidal unobstructed breathing from light, deep and rapid eye movement sleep were exported for quantitative analysis. Overnight polysomnography data from 45 PS [median age 4.4 years (interquartile range 3.0–7.7 years), OAHI 0 h −1 (0.0–0.2 h −1 )], 19 children with incWOB [age 2.8 years (2.4–5.7 years), OAHI 0.1 h −1 (0.0–0.4 h −1 )] and 27 children with OSA [age 3.6 years (2.6–6.2 years), OAHI 3.7 h −1 (2.3–6.9 h −1 )] were analysed. The sEMGcw was higher in those with OSA [8.47 μV (5.98–13.07 μV); P  < 0.0001] and incWOB [8.97 μV (5.94–13.43 μV); P <  0.001] compared with PS [4.633 μV (2.98–6.76 μV)]. There was no significant difference in the sEMGcw between children with incWOB and OSA ( P  = 0.78). Log sEMGcw remained greater in children with OSA and incWOB compared with PS after age, body mass index centiles, sleep stages and sleep positions were included in the mixed linear models ( P  < 0.0001). The correlation between sEMGcw and OAHI in children without OSA was small ( r s  = 0.254, P  = 0.04). The sEMGcw is increased in children with OSA and incWOB compared with PS. Abstract :